Reforming the funding of long-term care for older people: costs and distributional impacts of planned changes in England - Bo Hu; Ruth Hancock; Raphael Wittenberg; Derek King; Marcello Morciano (Health Economics, Policy and Law)
Reforms to the means tests in England for state-financed long-term care were planned for implementation in 2025. They included a lifetime limit (cap) on how much an individual must contribute to their care, with the state meeting subsequent care costs. We present projections of the costs and distributional impacts of these reforms for older people, using two linked simulation models which draw on a wide range of data. We project that by 2038 public spending on long-term care for older people in England would be about 14% higher than without the reforms. While the main direct beneficiaries of the lifetime cap would have been the better off who currently receive no state help with their care costs, the reforms also treated capital assets more generously than the current system, helping people with more modest incomes and wealth. When analysing the impacts of the reforms it is therefore important to consider the whole reform package. Our results depend on a range of assumptions, and the impacts of the reforms would be sensitive to the levels of the cap and other reformed parameters of the means test on implementation.